A Colorectal Cancer 3D Bioprinting Workflow as a Platform for Disease Modeling and Chemotherapeutic Screening - Sbirkov, Yordan; Molander, Diana; Milet, Clement; Bodurov, Ilia; Atanasov, Boyko; Penkov, Radoslav; Belev, Nikolay; Forraz, Nico; McGuckin, Colin; Sarafian, Victoria (Frontiers in Bioengineering and Biotechnology, 2021)
Colorectal cancer (CRC) is the third most common malignancy and has recently moved up to the second leading cause of death among carcinomas. Prognosis, especially for advanced disease or certain molecular subtypes of CRC, remains poor, which highlights the urgent need for better therapeutic strategies. However, currently as little as 0.1% of all drugs make it from bench to bedside because of the inherently high false positive and negative rates of current preclinical and clinical drug testing data. Therefore, the success of developing novel treatment agents lies in the introduction of improved preclinical disease models which resemble in vivo carcinomas closer, possess higher predictive properties, and offer opportunities for individualised therapy. Aiming to address these needs, we have established an affordable, flexible and highly reproducible 3D bioprinted CRC model. Histological assessment of Caco-2 cells in 3D bioprints revealed the formation of glandular-like structures which show greater pathomorphological resemblance to tumours than monolayer cultures do. RNA expression profiles in 3D bioprinted cells were marked by upregulation of genes involved in cell adhesion, hypoxia, EGFR/KRAS signaling and downregulation of cell cycle programmes. Testing this 3D experimental platform with three of the most commonly used chemotherapeutics in CRC (5-fluoruracil, oxaliplatin and irinotecan), revealed overall increased resistance compared to 2D cell cultures. Lastly, we demonstrate that our workflow can be successfully extended to primary CRC samples. Thereby, we describe a novel accessible platform for disease modelling and drug testing, which may present an innovative opportunity for personalised therapeutic screening.